Emergent Biomarkers of Residual Cardiovascular Risk in Patients with Low HDL-c and/or High Triglycerides and Average LDL-c Concentrations: Focus on HDL Subpopulations, Oxidized LDL, Adiponectin, and Uric Acid. (4th November 2013) - Mascarenhas-Melo, Filipa; Palavra, Filipe; Marado, Daniela; Sereno, José; Teixeira-Lemos, Edite; Freitas, Isabel; Isabel-Mendonça, Maria; Pinto, Rui; Teixeira, Frederico; Reis, Flávio
Abstract : This study intended to determine the impact of HDL-c and/or TGs levels on patients with average LDL-c concentration, focusing on lipidic, oxidative, inflammatory, and angiogenic profiles. Patients with cardiovascular risk factors (n = 169 ) were divided into 4 subgroups, combining normal and low HDL-c with normal and high TGs patients. The following data was analyzed: BP, BMI, waist circumference and serum glucose, Total-c, TGs, LDL-c, oxidized-LDL, total HDL-c and HDL subpopulations, paraoxonase-1 (PON1) activity, hsCRP, uric acid, TNF- α, adiponectin, VEGF, and iCAM1. The two populations with increased TGs levels, regardless of the normal or low HDL-c, presented obesity and higher waist circumference, Total-c, LDL-c, Ox-LDL, and uric acid. Adiponectin concentration was significantly lower and VEGF was higher in the population with cumulative low values of HDL-c and high values of TGs, while HDL quality was reduced in the populations with impaired values of HDL-c and/or TGs, viewed by reduced large and increased small HDL subfractions. In conclusion, in a population with cardiovascular risk factors, low HDL-c and/or high TGs concentrations seem to be associated with a poor cardiometabolic profile, despite average LDL-c levels. This condition, often called residual risk, is better evidenced by using both traditional and nontraditional CV biomarkers, including large and small HDL subfractions, Ox-LDL, adiponectin, VEGF, and uric acid.